2022
DOI: 10.3389/fgene.2022.906667
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Rare Homozygous RNASEH1 Mutations Associated With Adult-Onset Mitochondrial Encephalomyopathy and Multiple Mitochondrial DNA Deletions

Abstract: Mitochondrial DNA (mtDNA) maintenance disorders embrace a broad range of clinical syndromes distinguished by the evidence of mtDNA depletion and/or deletions in affected tissues. Among the nuclear genes associated with mtDNA maintenance disorders, RNASEH1 mutations produce a homogeneous phenotype, with progressive external ophthalmoplegia (PEO), ptosis, limb weakness, cerebellar ataxia, and dysphagia. The encoded enzyme, ribonuclease H1, is involved in mtDNA replication, whose impairment leads to an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study also concluded that in the presence of POLG-negative ataxia neuropathy spectrum, all patients should be considered for genetic analysis for RNASEH1 mutations since it is the fourth most common cause of adult mendelian PEO with multiple mtDNA deletions in their cohort, following POLG, TWNK and RRM2B [88]. Manini et al reported similar findings in their case report and compiled data from several reports of patients with the RNASEH1 mutation and noted that some of these frequent findings have been observed in other mitochondrial diseases, such as dysarthria in adults with POLG and TK2 mutations, and cerebellar signs in late-onset RRM2B mutations [87].…”
Section: Ribonuclease H1 (Rnase H1)mentioning
confidence: 65%
See 1 more Smart Citation
“…This study also concluded that in the presence of POLG-negative ataxia neuropathy spectrum, all patients should be considered for genetic analysis for RNASEH1 mutations since it is the fourth most common cause of adult mendelian PEO with multiple mtDNA deletions in their cohort, following POLG, TWNK and RRM2B [88]. Manini et al reported similar findings in their case report and compiled data from several reports of patients with the RNASEH1 mutation and noted that some of these frequent findings have been observed in other mitochondrial diseases, such as dysarthria in adults with POLG and TK2 mutations, and cerebellar signs in late-onset RRM2B mutations [87].…”
Section: Ribonuclease H1 (Rnase H1)mentioning
confidence: 65%
“…RNase H1, or ribonuclease H1, is an enzyme encoded by the gene RNASEH1, located in chromosome 17p11.2. This enzyme contributes to mitochondrial dynamics through primer maturation, removal, synthesis of replication primer, and pre-RNA processing in mtDNA replication [86,87]. In a cohort conducted by Bugiardini E. et al, patients harboring RNASEH1 mutations had characteristic features of CPEO, cerebellar ataxia, and dysphagia, with CPEO being a universal feature in all cases.…”
Section: Ribonuclease H1 (Rnase H1)mentioning
confidence: 99%